Pemanfaatan Limbah Kulit Nanas (Ananas comosus) Menjadi Sabun Cuci Piring Dengan Branding 'Nasclean' - Pamungkas, Putri Giat Dwi; Subagyo, Didik; Alfiyani, Helvi; Syifa, Intan Mauliana; Komalasari, Titin Karlina; Romadhona, Intan Rizky; Belynda, Shera Inez; Prasetiyo, Bayu; Hendryansyah, Amri; Saefuloh, Tabah; Wibawanti, Priandhita; Biky, Muhammad Amir; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
A community empowerment program in Karangsari Village, Pulosari District, Pemalang Regency, was carried out by utilizing pineapple peel waste (Ananas comosus) to produce liquid dishwashing soap branded "Nasclean". The program aimed to reduce environmental pollution caused by organic waste accumulation while creating business opportunities based on local potential. The implementation method included field surveys, socialization, training, and hands-on demonstrations with local housewives. The soap formulation used pineapple peel extract containing bromelain enzymes, flavonoids, saponins, and tannins as antibacterial and degreasing agents, combined with additional ingredients such as texapon, NaCl, and clean water. The results showed an increase in participants' knowledge and skills in processing organic waste into value-added products, as well as the production of high-quality soap with rich foam, a fresh natural aroma, and safe usage. This program had a positive ecological impact by reducing waste and an economic impact by opening opportunities for sustainable home- based businesses.